Headed into the Wind : A Memoir - Loeffler, Jack, 1936- (Book collections on Project MUSE., 2019)
"With the temperament of Santa Claus and the tenacity of a badger, Jack Loeffler reveals his compassion and concern for Southwestern traditional cultures and their respective habitats in the wake of Manifest Destiny. He speaks of his resistance to the corporate and political machinations that have turned the Southwest into the National Sacrifice Area in order to promulgate growth for the sake of growth. Working both as an individual and with comrades -- including Edward Abbey and Gary Snyder -- he was part of an early coterie of counterculturalists and hardcore radical environmentalists who fought to thwart the plunder of natural resources in the Southwest to serve presumed human needs. Loeffler, a former jazz musician, fire lookout, museum curator, bioregionalist, and self-taught aural historian, shares his humor and imagination, his adventures, observations, reflections, and meditations along the trail in his retelling of a life well-lived in the American Southwest. He also reveals the perspectives of authors, philosophers, scientists, and the salt of the Earth he has interviewed for his radio programs, sound collages, and books. In this honest memoir, he advises each and every one of us to go skinny-dipping joyfully in the flow of Nature to better understand where we're headed"--